Novel Anti-Inflammatory Approaches for Cystic Fibrosis Lung Disease: Identification of Molecular Targets and Design of Innovative Therapies - Mitri, Christie; Xu, Zhengzhong; Bardin, Pauline; Corvol, Harriet; Touqui, Lhousseine; Tabary, Olivier (Frontiers in Pharmacology, 2020)
Cystic fibrosis (CF) is the most common monogenic disorder among Caucasians, estimated to affect more than 70,000 people in the world. In patients with CF, the lack of cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel function causes mucus dehydration. This dehydration leads to diminishing mucociliary clearance of bacteria, resulting in severe and persistent bronchial inflammation and chronic bacterial infection that are hallmarks of CF lung disease and participate in its progression. Anti-inflammatory therapies are, therefore, of particular interest for CF lung disease. Furthermore, a better understanding of the molecular mechanisms involved in airways infection and inflammation in CF has led to the development of new therapeutic approaches that are currently under evaluation by clinical trials. These new strategies dedicated to CF inflammation are designed to treat different dysregulated aspects such as oxidative stress, cytokines secretion, remodeling, and the targeting dysregulated pathways. In this review, we summarize the current understanding of the molecular mechanisms by which airway epithelial cells contribute to abnormal lung inflammation in CF, as well as the new anti-inflammatory strategies proposed to CF patients by exploring novel molecular targets and novel drug approaches.